Boundary Work in Regulatory Controversies - Nigge, Karl-Michael (UnderCurrents: Journal of Critical Environmental Studies, 1996)
The regulation of technological risks is an area in which science and policy are generally linked in an inextricable fashion that Wynne aptly describes through the metaphor of the "regulatory jungle" (1992a). It involves a mixture of scientific, political and ethical issues, and due to the presence of scientific uncertainty on a significant scale, even the scientific issues cannot be answered by scientific means alone, but rely on policy considerations for their resolution. Seen from this perspective, controversies over technological risks come as no surprise. [...]